A Just and Durable Peace? American Evangelicals and the Quest for Peace after WWII. Issue 3 (3rd July 2019) - Joustra, Robert J.
Abstract: The force of evangelical activism is now a well-known story in American politics, but its unity, coherence, and perspective are often taken for granted, or under-analyzed, particularly on global issues. In this article, I investigate the question of evangelical influence and perspective on global peace after World War II, focused in this case around the United Nations. Surveying, first, the diversity of the movement called evangelicalism in the late war period, I argue that meaningful evangelical minorities existed, second, in both the neo-orthodox turn of Reinhold Niebuhr, third in the hugely successful though more mainline efforts of John Foster Dulles and the Federal Council of Churches, and, of course, finally in the majority report of conservative, evangelical anti-globalism, of both dispensational and presuppositional varieties. Far from monolithic, I argue that an evangelical perspective and influence on global peace must read each of these movements alongside one another, in part clarifying, in part unsettling, what is often counted as evangelical in both the history and present of global peace.